2017
DOI: 10.1530/ec-17-0294
|View full text |Cite
|
Sign up to set email alerts
|

Exenatide modulates tumor–endothelial cell interactions in human ovarian cancer cells

Abstract: Diabetes and cancer are prevalent diseases whose incidence is increasing globally. Diabetic women have a moderate risk increase in ovarian cancer, suggested to be due to an interaction between these two disorders. Furthermore, patients manifesting both diseases have associated worse prognosis, reduced survival and shorter relapse-free survival. According to current recommendations, incretin drugs such as Exenatide, a synthetic analog of Exendin-4, and Liraglutide are used as therapy for the type 2 diabetes (T2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…As previously reported, the GLP-1R agonist inhibited TNFα/LPS-induced THP-1 monocyte-endothelial adhesion via reduction of the protein expression of adhesion molecules VCAM-1 [32]. Similarly, GLP-1 analog also modulated tumor-endothelial cell interactions through reducing production of adhesion molecules (ICAM-1 and VCAM-1) [33]. Additionally, the GLP-1 analog suppressed the expression of cell adhesion molecules including ICAM-1 and VCAM-1 in diabetic We previously demonstrated that mice with LPS-induced ALI benefited from Rho inhibition [24].…”
Section: Discussionsupporting
confidence: 69%
“…As previously reported, the GLP-1R agonist inhibited TNFα/LPS-induced THP-1 monocyte-endothelial adhesion via reduction of the protein expression of adhesion molecules VCAM-1 [32]. Similarly, GLP-1 analog also modulated tumor-endothelial cell interactions through reducing production of adhesion molecules (ICAM-1 and VCAM-1) [33]. Additionally, the GLP-1 analog suppressed the expression of cell adhesion molecules including ICAM-1 and VCAM-1 in diabetic We previously demonstrated that mice with LPS-induced ALI benefited from Rho inhibition [24].…”
Section: Discussionsupporting
confidence: 69%
“…Indeed, the GLP-1 receptor agonist Exendin-4 has been reported to decrease proliferation of prostate cancer cells by a PKA-dependent mechanism, and attenuate prostate cancer growth in a tumor xenograft mouse model (42). Exendin-4 was also shown to inhibit migration and promote apoptosis in ovarian cancer cells (43). Therefore, PKA-dependent inactivation of CaMKK2 may provide a potential mechanism for the anti-proliferative effects of Exendin-4 in both prostate and ovarian cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the induction of apoptosis was confirmed by fluorescent techniques using the caspase-3/7 detection reagent. Treatment with the FHRH extract resulted in bright fluorescent nuclei (Figure 4), a hallmark of cells undergoing apoptosis [34].…”
Section: Discussionmentioning
confidence: 99%